2021
DOI: 10.1371/journal.pone.0256818
|View full text |Cite
|
Sign up to set email alerts
|

HAV infection in Brazilian men who have sex with men: The importance of surveillance to avoid outbreaks

Abstract: Background Hepatitis A is a fecal-oral infection caused by hepatitis A virus (HAV). Men who have sex with men (MSM) and transgender women (TW) have been reported as target groups for HAV infection. This study aimed to determine the seroprevalence, risk factors, and circulating strains associated with HAV infection among MSM and TW in Central Brazil. Methods A cross-sectional study was conducted from November 2011 to September 2013. Serum samples were collected from 425 individuals for anti-HAV antibody testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(41 reference statements)
3
6
0
Order By: Relevance
“…The predominance of male gender (78.85%) has similarly been reported in other studies [11,13,35,36] and the Brazilian Ministry of Health Viral Hepatitis Bulletin [17,18]. Studies have reported sexual practices as significant risk factors for HAV infection, with the practices of oral, oroanal, and anal sex as important transmission routes [32][33][34][35]37]. Likewise, recent Brazilian studies suggested that the increased HAV incidence in Brazil could be associated with sexual practices between men [10,38].…”
Section: Discussionsupporting
confidence: 66%
“…The predominance of male gender (78.85%) has similarly been reported in other studies [11,13,35,36] and the Brazilian Ministry of Health Viral Hepatitis Bulletin [17,18]. Studies have reported sexual practices as significant risk factors for HAV infection, with the practices of oral, oroanal, and anal sex as important transmission routes [32][33][34][35]37]. Likewise, recent Brazilian studies suggested that the increased HAV incidence in Brazil could be associated with sexual practices between men [10,38].…”
Section: Discussionsupporting
confidence: 66%
“…Unfortunately, data on HAV among TGW in Brazil are scarce. Recently, in another city in Central Brazil, Castro et al [ 20 ] reported an overall anti-HAV prevalence of 69.7%, ranging from 62.3% among MSM ( n = 276) to 83.2% among TGW ( n = 149). Among MSM aged ≤20 years, 60% were HAV-susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Among MSM aged ≤20 years, 60% were HAV-susceptible. In addition, Castro et al [ 20 ] observed one TGW who was anti-HAV-IgM-positive and, thus, a potential HAV disseminator in her network. She was aged 21 years, reported sex work, alcohol, and drug use, and did not use a condom during oral sex.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of participants was undertaken between September 30, 2021 and June,19 2023 by convenience sampling as participants attended scheduled PrEP visits at IMT-RN. The sample size was calculated using the website OpenEpi ( https://www.openepi.com/SampleSize/SSPropor.htm ), based on the prevalence of 62.3% for total anti-HAV antibodies among MSM [ 19 ], confidence limits of ± 6%, 5% of α-error and 20% of β-error. The study should include at least 251 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…MSM are not included in the Brazilian immunization program. The HAV seroprevalence among MSM varies from 37.0% in Amsterdam to 62.3% in Central Brazil [ 18 , 19 ]. However, population immunity levels > 70% are needed to prevent outbreaks among MSM [ 20 ].…”
Section: Introductionmentioning
confidence: 99%